The Authority of Judges in Applying Diversion to Children Facing Criminal Charges Carrying a Sentence of More Than Seven Years - Redi Pirmansyah; Arifin, Muhammad Zainul; M. Iqbal (JUSTISI, 2026)
The aim of this study is to analyze the implementation of diversion in juvenile crimes based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law). The study method uses a normative legal method through a case study of legal behavior products. The novelty of this research lies in its in-depth analysis of the authority of judges in determining diversion for criminal acts with a maximum penalty of more than 7 years. Although normatively excluded by the UU SPPA, this is interpreted progressively using a restorative justice approach and the principle of the best interests of the child. The results of the research examine the discretion of judges in applying the principle of restorative justice in serious criminal cases that, according to the standard rules, are not eligible for diversion. Through a normative approach and empirical case studies, this research provides new insights and recommendations for reformulating more humane legal policies. The aim is to make the justice system more responsive to the protection of children's rights in accordance with national legal standards. Conclusion This study found that diversion under the SPPA is limited to criminal offenses carrying a sentence of less than seven years. However, Supreme Court Regulation (Perma) No. 4 of 2014 expands this scope, particularly in the case of mixed charges. This regulatory discrepancy creates a dilemma for judges in determining the appropriate legal reference. This inconsistency has an impact on legal uncertainty, where similar cases can receive different diversion treatments. Therefore, harmonization between the Supreme Court regulation and the SPPA Law is urgently needed to ensure equal justice for children.